Engineering Innovations Vol. 7 - Afrooz Barnoush; Elena Gordo Odériz; Dong Keon Kim; Yurii Otrosh; Omar S. Dahham; Manoj A. Kumbhalkar (Trans Tech Publications Ltd, 2023)
The 7th volume of the journal Engineering Innovations contains articles that accent the reader's attention on the latest engineering design and results of research in materials science, engineering design, urban transport network development issues, wastewater treatment, investigation of thermophysical properties of alternative engine fuel, etc. The presented articles will be helpful to many engineers and researchers in materials, mechanical engineering, civil engineering and environmental protection.